2009
DOI: 10.1371/journal.pntd.0000571
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Infection with Trypanosoma cruzi and Congenital Chagas Disease Induce a Trend to a Type 1 Polarization of Infant Immune Responses to Vaccines

Abstract: BackgroundWe previously showed that newborns congenitally infected with Trypanosoma cruzi (M+B+) display a strong type 1 parasite-specific T cell immune response, whereas uninfected newborns from T. cruzi-infected mothers (M+B−) are prone to produce higher levels of proinflammatory cytokines than control neonates (M−B−). The purpose of the present study was to determine if such fetal/neonatal immunological environments could alter the response to standard vaccines administered in early life.MethodologyInfants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 48 publications
6
28
0
1
Order By: Relevance
“…In addition, the large sub-population of parasite-uninfected mDCs activated during incubation with T. cruzi could process and present extracellular parasite antigens, as well as a large variety of T. cruzi-unrelated antigens for which immune responses would be boosted. This is supported by our previous report showing that 6-to 7-month-old infants born to T. cruzi-infected mothers display improved type 1 immune responses to BCG, HBV, diphtheria and tetanus vaccines after standard immunization [11].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, the large sub-population of parasite-uninfected mDCs activated during incubation with T. cruzi could process and present extracellular parasite antigens, as well as a large variety of T. cruzi-unrelated antigens for which immune responses would be boosted. This is supported by our previous report showing that 6-to 7-month-old infants born to T. cruzi-infected mothers display improved type 1 immune responses to BCG, HBV, diphtheria and tetanus vaccines after standard immunization [11].…”
Section: Discussionsupporting
confidence: 83%
“…One to 12% of T. cruzi-infected pregnant women transmit the parasite to their foetuses [7,8]. In previous studies, we showed that: (i) uninfected newborns from T. cruzi-infected mothers display a potent inXammatory environment [50], (ii) newborns congenitally infected with T. cruzi develop an adult-like parasite-speciWc CD8 + T cell response producing interferon(IFN)- [16] and (iii) 6-to 7-month-old infants born to T. cruzi-infected mothers displayed boosted type 1 immune responses to Bacillus Calmette Guerin (BCG), hepatitis B virus (HBV), diphtheria and tetanus vaccines after routine immunization [11]. These data point out a T. cruzi-associated immunological imprinting of immune responses in early life by maternal and/or congenital infection, overcoming immunological immaturity in early life and resulting in parasite-speciWc as well as boosted heterologous responses, such as those mounted to vaccine antigens.…”
Section: Introductionmentioning
confidence: 99%
“…It includes antibodies recognizing T. cruzi (Miles et al, 1975;Breniere et al, 1983;Truyens et al, 2005;Sosa-Estani et al, 2008), as well as other microorganisms having previously infected the woman, or resulting from vaccinations (Dauby et al, 2009). The levels of T. cruzi-specific-antibodies in neonates and their repertoire are similar to those of their mothers (Breniere et al, 1983), indicating that the slight and focused placentitis often observed in chronically infected pregnant women (see Sections 6.2 and 6.3) does not affect their transfer.…”
Section: Main Immunologically Relevant Transferred Moleculesmentioning
confidence: 99%
“…or uninfected mothers (without T. cruzi-specific antibodies; Ab-), obtained in Bolivia from previous studies [4,33]. IgG were purified by three sequential precipitations with ammonium sulfate 33% (w/w) final concentration, washed, dialyzed against PBS, and stored in small aliquots at -20°C at a concentration of 10 mg/mL until use (to avoid IgG aggregation after repeated thawing).…”
Section: Purification Of Iggmentioning
confidence: 99%